Social Activity and Cognitive Functioning Over Time: A Coordinated Analysis of Four Longitudinal Studies. (9th September 2012) - Brown, Cassandra L.; Gibbons, Laura E.; Kennison, Robert F.; Robitaille, Annie; Lindwall, Magnus; Mitchell, Meghan B.; Shirk, Steven D.; Atri, Alireza; Cimino, Cynthia R.; Benitez, Andreana; MacDonald, Stuart W. S.; Zelinski, Elizabeth M.; et al.
Abstract : Social activity is typically viewed as part of an engaged lifestyle that may help mitigate the deleterious effects of advanced age on cognitive function. As such, social activity has been examined in relation to cognitive abilities later in life. However, longitudinal evidence for this hypothesis thus far remains inconclusive. The current study sought to clarify the relationship between social activity and cognitive function over time using a coordinated data analysis approach across four longitudinal studies. A series of multilevel growth models with social activity included as a covariate is presented. Four domains of cognitive function were assessed: reasoning, memory, fluency, and semantic knowledge. Results suggest that baseline social activity is related to some, but not all, cognitive functions. Baseline social activity levels failed to predict rate of decline in most cognitive abilities. Changes in social activity were not consistently associated with cognitive functioning. Our findings do not provide consistent evidence that changes in social activity correspond to immediate benefits in cognitive functioning, except perhaps for verbal fluency.